Associated Risk Factors for Depression in MDR-TB Patients Receiving Cycloserine Therapy at dr. Soebandi Regional Hospital - Maulidiyah, Najma; Wisudanti, Desie Dwi; Rachmawati, Dwita Aryadina; Komariah, Cicih; Raharjo, Angga Mardro (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: The most common psychological disorder in cycloserine treatment is depression. The purpose of this study was to identify the risk factors associated with depression in MDR-TB patients receiving cycloserine therapy at dr. Soebandi Regional Hospital. Data were obtained from medical records and the Depression Anxiety Stress Scales (DASS-42) questionnaire from 89 MDR-TB patients at dr. Soebandi Regional Hospital in 2022-2024. Methods: Data analysis was performed using the Lambda and Somers’ tests, followed by multivariate analysis using ordinal logistic regression. Results: Out of a sample of 89 patients, 27 (30.3%) experienced depression, with the majority experiencing moderate-level depression (18%). The bivariate test results showed that the variables that significantly influenced the level of depression were gender (P=0.011), education (P=0.000), occupation (P=0.037), BMI (P=0.000), and comorbidities (P=0.029). Multivariate tests showed that three variables had a significant effect (P<0.05) on the level of depression: gender (P=0.047), occupation (P=0.001), and comorbidities (P=0.011). The top two dominant risk factors affecting the level of depression are occupation (OR=17.12) and comorbidities (OR=9.14). Conclusion: Occupation and comorbidities are the risk factors that most influence the level of depression in MDR-TB patients receiving cycloserine.